Academic Profession And University In The Context Of The Historical Role Of Higher Education - Ismoilov Temurbek Islomovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
When considering the various transformations of universities and the academic profession, it is useful to study the process of the emergence and development of higher education systems in historical dynamics. In discussions about the problems of the scientific profession, as a rule, the image of the university arises, and vice versa. This relationship is primarily due to the institutional genesis of science as a social phenomenon